2012
DOI: 10.1186/1471-2377-12-45
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cardiovascular exercise early after stroke: systematic review and meta-analysis

Abstract: BackgroundPrevious studies have shown the beneficial effects of aerobic exercise in chronic stroke. Most motor and functional recovery occurs in the first months after stroke. Improving cardiovascular capacity may have potential to precipitate recovery during early stroke rehabilitation. Currently, little is known about the effects of early cardiovascular exercise in stroke survivors. The aim of this systematic review was to evaluate the effectiveness of cardiovascular exercise early after stroke.MethodsA syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(108 citation statements)
references
References 52 publications
3
97
0
8
Order By: Relevance
“…9,34 The magnitude of changes in VO 2 max among stroke patients is similar to healthy sedentary adults or participants in cardiac rehabilitation (12.5% versus 10% to 30% versus 13% to 15%, respectively). 35 Even if the observed improvements are small in absolute terms (eg, ≈1 mL/kg/min), 36 considering low baseline fitness levels, the same improvements can have significant functional carryover for stroke survivors. In addition to improved cardiorespiratory capacity, one systematic review 36 supported the idea that AE improves gait velocity and capacity in randomized trials involving ≤133 mildly to moderately affected stroke patients.…”
Section: Aerobic Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…9,34 The magnitude of changes in VO 2 max among stroke patients is similar to healthy sedentary adults or participants in cardiac rehabilitation (12.5% versus 10% to 30% versus 13% to 15%, respectively). 35 Even if the observed improvements are small in absolute terms (eg, ≈1 mL/kg/min), 36 considering low baseline fitness levels, the same improvements can have significant functional carryover for stroke survivors. In addition to improved cardiorespiratory capacity, one systematic review 36 supported the idea that AE improves gait velocity and capacity in randomized trials involving ≤133 mildly to moderately affected stroke patients.…”
Section: Aerobic Exercisementioning
confidence: 99%
“…35 Even if the observed improvements are small in absolute terms (eg, ≈1 mL/kg/min), 36 considering low baseline fitness levels, the same improvements can have significant functional carryover for stroke survivors. In addition to improved cardiorespiratory capacity, one systematic review 36 supported the idea that AE improves gait velocity and capacity in randomized trials involving ≤133 mildly to moderately affected stroke patients. This benefit may be even more evident with task-oriented therapy (ie, strengthening the lower extremities, enhancing walking balance and speed, or treadmill walking at higher intensity) reported in 2 randomized controlled trials with exercise sessions performed for 6 weeks (n=91; >1 year poststroke) 37 and 6 months (n=91; >6 months poststroke).…”
Section: Aerobic Exercisementioning
confidence: 99%
“…Although aerobic exercise has been shown to improve cardiovascular fitness in people with stroke (Stoller, de Bruin, Knols, & Hunt, 2012), its potential role in enhancing neuroplasticity and motor recovery after stroke has not been examined.…”
mentioning
confidence: 99%
“…There is strong evidence that aerobic exercise (40-50% HRR progressing to 60-80%) conducted 20-40 min and 3-5 days per week is beneficial for enhancing aerobic fitness, walking speed and walking endurance in people who have had mild to moderate stroke and are deemed to have low cardiovascular risk with exercise after proper screening assessments (grade A recommendation). 17 observed effects of cardiovascular exercise early after stroke: systematic review and meta-analysis from 11 trials (10 RCT or randomized controlled pilot studies, 1 study prospective controlled matched design) with 423 participants. Results showed that Peak oxygen uptake (n=155) favoring the intervention group (SMD = 0.83, CI95% = 0.50-1.16, Z = 4.93, P<0.01).…”
Section: Resultsmentioning
confidence: 99%